Reconstructing Boundaries of Spousal Interaction with the Opposite Sex in the Digital Era: A Sadd Al-Dzari'ah Approach in Islamic Family Law - Agung Gunawan; Emha Hasan Nashrulloh; Noor Naemah Abdul Rahman; Ozioma Victoria Uchime (An-Nisa: Journal of Islamic Family Law, 2026)
The high divorce rate in Indonesia, which reached 516,334 cases in 2022, shows the increasingly vulnerable resilience of Muslim families. Previous studies have generally explained divorce from social, economic, and psychological perspectives, while studies that have formulated preventive limits on the interaction of husband and wife with the opposite sex based on Islamic legal principles, especially in physical, digital, and professional spaces, are still very limited. This study aims to formulate preventive limits on the interaction of husband and wife with the opposite sex based on the concept  of sadd adz-dzarī'ah in the perspective of Islamic Family Law and analyze its normative capacity as a basis for strengthening Muslim family governance in the modern era. This research uses a normative legal research method based on literature studies with a conceptual approach and maqāṣid al-syarī'ah. The data was analyzed qualitatively through the study of the Qur'an, hadith, classical literature of uṣūl fiqh, and contemporary scientific publications. The results of the study show that sadd adz-dzarī'ah has a strong and proportionate normative capacity because it only limits interactions that objectively have a high potential to lead to acts that are prohibited by the Shari'ah. This research produced a Preventive Model of Three Spaces of Interaction that includes the boundaries of physical, digital, and professional interactions, accompanied by measurable indicators of the shift in interaction from the category of mubāḥ to dzarī'ah as well as a multi-level normative classification that includes mubāḥ, makrūh, and ḥarām. These findings expand the scope of the study of fiqh mu'āsyarah into the digital space as a theoretical contribution that has not been widely discussed in the literature before. This study recommends that the model be integrated into the curriculum of marriage guidance, family education, and Muslim family development policies as preventive instruments to strengthen family resilience in the digital age.